2023
DOI: 10.1177/00219983231176025
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effects of lignin and cellulose nanofibers on the properties of starch/zein blends

Abstract: The study aimed to develop cornmeal-based thermoplastic composites by using corn starch and zein (the two major components of cornmeal) as the matrix and lignin as the compatibilizer, while cellulose nanofibrils (CNFs) served as the reinforcement. The research examined the individual effects of lignin and CNFs on the mechanical properties of the composites. Two parts of lignin decreased the domain size of the blend and increased the strength and modulus by 31% and 44%, respectively. Six parts of CNFs led to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…As discussed in our previous study, the increases can be attributed to the synergetic reinforcement effect of the lignin and CNFs. 1 Lignin nanoparticles in the starch-zein blend have been shown to refine the phase structure of the blend and increase the compatibility of the two phases, leading to improved mechanical properties. CNFs as a nanofibrous material are known to significantly reinforce biopolymers at low fiber concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As discussed in our previous study, the increases can be attributed to the synergetic reinforcement effect of the lignin and CNFs. 1 Lignin nanoparticles in the starch-zein blend have been shown to refine the phase structure of the blend and increase the compatibility of the two phases, leading to improved mechanical properties. CNFs as a nanofibrous material are known to significantly reinforce biopolymers at low fiber concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we increased the mechanical properties of TPS by incorporating zein, lignin, and cellulose nanofibers (CNFs) into the bioplastic through extrusion. 1 We showed that lignin improved the dispersion of zein and reduced its particle size in the TPS matrix by functioning as a compatibilizer, leading to increased strength and modulus of the composites. The addition of CNFs, an effective reinforcement for natural polymers, also significantly improved the composite properties.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations